Achieving uniform hardness in additively manufactured TA15 alloy via Ni or Cu additions - Leyu Cai; Yaojia Ren; Xinyan Liu; Min Song; Ian Baker; Hong Wu (Materials Research Letters)
The coarse columnar grains that typically occur during additive manufacturing introduce mechanical anisotropy. Both to achieve a columnar-to-equiaxed transition (CET) and to investigate the effects of high growth restriction factor elements on the hardness distribution, this study introduced Ni and Cu into TA15 via laser directed energy deposition (LDED). The resulting as-built structures exhibited both equiaxed grains and uniform hardness. The CET, greater variety of grain orientations, differences in α′-phase variants and alterations in slip system and residual stress contributed to this uniformity. This research provides insights into designing isotropic LDED titanium alloys.